Metafora dalam Lirik Lagu “Mendarah” oleh Nadin Amizah - Ayudia Helmi; Widya Utari; Adelliya Yuwanda Putri; Frinawaty Lestarina Barus; Alya Luthifah (Lingua Susastra, 2021)
The use of literary techniques such as metaphor is commonly found in imaginative writing such as song lyrics. In addition, metaphors can enrich the aesthetic and atmospheric elements in a musical work. This study aims to discuss the element of metaphor in the lyrics of the song "Mendarah" by Nadin Amizah. This research is a qualitative research with descriptive method. Data collection techniques were carried out through observation and note-taking methods. Data analysis was carried out using a direct-directed content analysis method. Analysis of the use of metaphors in the lyrics of this song can be implied in the semantic perspective. The results of this study indicate that there are 3 explicit metaphors (in praesentia) and implicit metaphors (in absentia) in the song "Mendarah". The selection of explicit metaphors (in praesentia) and implicit metaphors (in absentia) have been proportioned in such a way as to produce songs that are not only good to listen to, but also able to convey the message contained in them.